The Geometries of Stable Isotopes in Tooth Enamel and Their Radiation Cycles and Archaeological Significance - Mergen, Atiye Bahar; Yılmaz, Mücahıt; Karabulut, Ezman; Celik, Fatih Ahmet (My University, 2023)
Archaeologically, the elements in the tooth enamel and their isotopes provide a lot of information about the related period, such as the way of life and nutrition culture. In this study, it was determined how the durability or brittleness of tooth enamel varies with the presence of H, C, N and S elements, which are mostly detected in tooth enamel, and their most stable isotopes, D (deuterium), 13C, 15N, 34S elements. These elements were moved inside and on the surface of the hydroxyapatite (HAp) crystal, which is the most abundant in tooth enamel and the cornerstone of enamel. At the end of the study, it was revealed that Nitrogen (N) and Sulphur (S) elements, especially Ca atoms that ensure the durability of the HAp crystal, and Oxygen atoms make bonds that prevent electronic charge sharing. In addition, this type of bonding (in geometries holding many Ca atoms) increase the fragility as the number of Ca-O bonds decrease. At the same time, such bindings create difficulties in determining the isotopes of the relevant elements. C bonding, on the other hand, provides a strong stretching action as it provides a double bond with the Oxygen atom, so the isotopic state of the carbon atom easily shows itself. The same situation was observed for element H and its isotope D. These findings better explain the brittleness of the teeth of ancient people, especially those who were fed marine life. Keywords: Carbon, Hydrogen, Hydroxyapatite, Nitrogen, Sulphur
Keywords: Hydroxyapatite; Hydrogen; Nitrogen; Carbon; Sulphur